1999
DOI: 10.1038/sj.onc.1203243
|View full text |Cite
|
Sign up to set email alerts
|

Gli genes in development and cancer

Abstract: With the realization that many proto-oncogenes and tumor suppressor genes are expressed and have important functions during mammalian development, it is clear that cancer often involves the inappropriate activation of genetic pathways used during normal development. A signaling cascade that has been of considerable interest to both developmental and cancer biologists involves the Hedgehog (Hh) family of secreted proteins. To date, the only transcription factors shown to be directly downstream of Hh are the zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(110 citation statements)
references
References 84 publications
2
105
0
1
Order By: Relevance
“…However, Gli-2 and Gli-3 could function either as oncogenes or tumor suppressors, depending on the type of mutation and cellular context. 6 However, Gli-2 is known to have a redundant function with Gli-1 and has been implicated in tumorigenesis. 2 According to our results, Gli-2 may play a more important role than Gli-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Gli-2 and Gli-3 could function either as oncogenes or tumor suppressors, depending on the type of mutation and cellular context. 6 However, Gli-2 is known to have a redundant function with Gli-1 and has been implicated in tumorigenesis. 2 According to our results, Gli-2 may play a more important role than Gli-1.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Gli-2 and Gli-3 function as oncogenes or tumor suppressors, depending on the type of mutation and cellular context. 6 The deregulation of Hh-signaling pathway has been implicated in several types of cancers. [2][3][4] The mutational activation of the Hh-signaling pathway, whether sporadic or in Gorlin's syndrome, is associated with tumorigenesis in a small subset of these tissues, predominantly skin, the cerebellum, and skeletal muscle.…”
mentioning
confidence: 99%
“…30,31 Gli proteins mediate transcriptional responses to Hedgehog family members, 19,20 and the Gli2⌬C4 transactivation-domain mutant blocks Gli func-tion in a dominant-negative manner. 22 To inhibit Hedgehog signaling selectively in cutaneous epithelium, we used the bovine K5 promoter 23 to generate K5-Gli2⌬C4 transgenic mice.…”
Section: Resultsmentioning
confidence: 99%
“…We Âźnd that overexpression of Xmeis1 in ectodermal explants induces XGli-3 and XZic3 expression, while XGli-1 is not a ected (Figure 4). Gli and Zic genes, like Xmeis1b, induce neural tissue in animal cap explants (Nakata et al, 1997;Ruizi Altaba, 1998;Brewster et al, 1998;Matise et al, 1998;Ding et al, 1998) and it is interesting that Xmeis1b induces XGli-3 which is normally expressed in dorsal neural tube from where neural crest emanates (Marine et al, 1997), but does not induce XGli-1 which is found ventrally within the neural tube. Moreover, transverse sections revealed that Xmeis1b induced an accumulation of ectopic pigmented cells in the embryo, and pigmented cells are often derived from neural crest.…”
Section: Discussionmentioning
confidence: 99%